Neonatal Tetanus After Home Delivery: Report of One Case - Shou-Chih Chang; Chun-Lung Wang (Elsevier, 2010)
Neonatal tetanus is a rare disease in developed countries, but remains common in developing countries. Pregnant women immigrating to Taiwan from developing countries may carry a risk of neonatal tetanus to the child, because of inadequate tetanus toxoid immunization and inappropriate postnatal cord care. Many young pediatricians in Taiwan are unfamiliar with this disease. Herein, we describe the clinical course of a newborn with neonatal tetanus, who was admitted with complaints of difficult feeding and muscle rigidity. After mechanical ventilation for 58 days and a prolonged hospital stay, the infant was discharged in good condition. It is important to maintain a high index of suspicion for neonatal sepsis when infants present with seizure-like symptoms, in order to allow its early diagnosis and appropriate treatment.